Infrared Spectroscopy of Neutral C7H7 Isomers: Benzyl and Tropyl - Satink, Rob G; Meijer, Gerard; von Helden, Gert (Journal of the American Chemical Society, 2003)
The gas-phase infrared absorption spectra of neutral benzyl and tropyl, isomers of formula C7H7, have been measured in the 400−1800 cm-1 spectral region. In addition, a quantum chemical calculation has been performed to model the infrared spectra. For the benzyl radical, the theory shows satisfactory overlap with the experiment, although vibrations involving the CH2 group might be anharmonic. The tropyl radical, which is subject to the Jahn−Teller effect, seems well modeled for the out-of-plane vibrational modes, but less so for the in-plane vibrational modes.